The Role of Positive Vibes in Preventing Academic Stres Among MTsN 1 Palangka Raya Students - Nor Alvanajati; Hamdanah; Surawan (Universitas PGRI Yogyakarta, 2025)
Academic stress is an internal pressure experienced by students due to demands in the learning environment that feel heavy. Therefore, students need to have the ability to always positive feelings, so that they are not easily stressed due to academic pressure.This study aims to explore the role of positive vibes in preventing academic stress in students of MTsN 1 Palangka Raya. The study used a descriptive qualitative approach with the subject of 10 superior VIII grade students. Data were collected through observation, interviews, and documentation. Result show that relaxation techniques, time management, and self-healing effectively reduce stress. Methods for building positive vibes include having broad insights , emotional regulation, and inspiring others. This implementing these methods in modern educational settings. Keywords: academic stress, positive vibes, prevention